ASSESSMENT OF AXIOLOGICAL POTENTIAL IN FUTURE TEACHERS AND THEIR INDICATORS - hodjaev, Begzod; Mekhmonova, Jamila (Educational Research in Universal Sciences, 2023)
In this article, in the education of a perfect person, based on life experiences, he entered the system of social sciences within the framework of phenomena that teach the laws, principles and methods of forming a high spiritual meaning, having its theoretical, national and practical foundations, theoretical foundations of pedagogy It is based on the general rules and principles of education and training of a perfect person, relying on the rich experience created by the people, theoretical and methodical sources of scientific research, the works of enlightened thinkers of Central Asia and the world, aimed at human perfection. For this purpose, the national heritage of each nation is connected with universal, universal human values. In different periods of the development of the society, the conceptual foundations of family education were considered to be universal values, as well as the problems of forming such qualities as correctness, honor, dignity, kindness, humanity and hard work, and the ability to respond to kindness with kindness.